Public trust and state management of the COVID-19 pandemic in Nigeria - Abayomi, Kolapo Quadri (Frontiers in Political Science, 2024)
The COVID-19 pandemic generated an unprecedented global crisis with long-lasting consequences. In this study, I examine the bi-directional nexus between public trust and the management of the pandemic in Nigeria. I argue that there is a relationship between government management of public policies and the level of public trust. The research draws on the Theory of Trust, in-depth interviews (IDI), and focus group discussions (FGD) and is supported by other secondary sources. I found that the main reason for citizens’ resistance to major policies introduced to contain the spread of the pandemic was due to an entrenched lack of trust in the government, its agencies, and officials. The findings also indicate that a lack of transparency and accountability in the management of the pandemic deepened the already fractured public trust. This was particularly visible in the shrouded pattern of disbursing cash transfers, allegations of corruption against the managers of the pandemic, and evidence of concealed palliatives meant to cushion the negative economic effects of the pandemic. The article recommends that the government needs to promote public trust by adopting an open governance approach that institutionalises transparency and accountability, fosters constant and consistent citizen engagement on government policies and programmes, strengthens critical agencies, and engenders a sense of belonging for all citizens.